MEDIA DAN WACANA: TELAAH KETERBUKAAN INFORMASI PUBLIK DI PROVINSI JAWA BARAT - Dedi Kurnia S. Putra (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2018)
The relation of interest between Pikiran Rakyat (HUPR) and West Java Provincial Government (WestJava Provincial Government), especially in the case of public information disclosure, became animportant focus in this research. Through the discourse study formulated by Teun A. Van Dijk, thisresearch seeks to reveal how the HUPR plays a role in the production of news discourse. Then, theissue of this discourse is seen from Gramsci's assumption of hegemony. Some of the findings lead to apattern of mutual interest, both HUPR and West Java Provincial Government. The interest is in theform of image and reputation related to information disclosure on the side of the power of government,and the economic side of the circulation of advertising suppliers in HUPR by the Government from theside of HUPR. Of course, the interest, established because of the pull of power in producinginformation that later in the consumption by the public on a permassive basis. Furthermore, theseconditions resulted in the finding that the greatest cooptation was successfully carried out by theGovernment, while the HUPR had no significant power in drafting its own discourse, as it had beensystematically dictated by the Government, both economically, politically and socially. This researchconfirms that HUPR does not perform its function as sharing information as knowledge, but only as amedium or a tool of government power in creating legitimacy of reputation as an open government.Gramsci through the theory of Hegemony (1991) believes that the government will use all resources topreserve its power. And that power was conseptualized by Van Dijk through the construction of mediadiscourse. With this assumption, then what is happening between HUPR and the government is amutual attraction of interests related to power in each corridor. Media with the interests of capital,and the government with the interests of reputation and image.